Robust Hepatic Gene Silencing for Functional Studies Using Helper-Dependent Adenoviral Vectors - Ruiz, Rafaela (Mary Ann Liebert, Inc., 2009)
RNA interference is currently envisioned as the basis of gene function and drug target validation studies. This novel technology has the advantage of providing a remarkably faster tool for gene silencing than traditional transgenic animal methodologies. In vivo administration of short interfering RNA (siRNA) typically results in reduced target gene expression for approximately 1 week. Viral vectors offer the possibility to express constitutive levels of short hairpin RNA (shRNA) so that the effects of knocking down the target gene can be studied for a few weeks, rather than a few days. Helper-dependent vectors have a significant advantage over previous generations of adenoviral vectors because of their much higher cloning capacity, potential for long-term transgene expression, and enhanced safety profiles on administration in vivo. Therefore, this advanced type of vector is an excellent tool to carry out in vivo studies directed at constitutive expression of shRNA. Here we show it is possible to obtain more than 90% target gene knockdown in an animal model of type 2 diabetes for several weeks, thereby consolidating this technology as an alternative to generating liver-specific knockout animals.